Faktor-Faktor yang Mempengaruhi Tingkat Pengungkapan Laporan Berkelanjutan Perusahaan di Bursa Efek Indonesia Tahun 2022 - Andri Yuniansyah Prihandono; Yudhi Herliansyah (Owner : Riset dan Jurnal Akuntansi, 2025)
An examination was conducted to investigate how Return on Assets (ROA), Company Size, Company Age, and Foreign Ownership influence Sustainability Report disclosure levels among companies listed on the Indonesia Stock Exchange (IDX) in 2022. The study employed a quantitative methodology using multiple linear regression analysis on 192 firms that published sustainability reports based on the 2021 Global Reporting Initiative (GRI) standards. The findings reveal that neither ROA nor Foreign Ownership significantly affects the level of sustainability disclosure. In contrast, Firm Size and Firm Age significantly positively correlate with sustainability disclosure practices. These results are in line with stakeholder and legitimacy theories, as larger and older companies tend to be more responsive to stakeholder demands and regulatory expectations regarding sustainability. Furthermore, this research highlights how the adoption of GRI 2021, which imposes more comprehensive and detailed reporting requirements, may influence disclosure behaviors, particularly for firms with limited resources or foreign ownership. This study contributes to the growing body of literature by identifying key determinants affecting sustainability reporting under the latest GRI framework. However, the research is limited to companies voluntarily adopting GRI 2021 standards, which may not fully represent all IDX-listed firms. Future research should consider broader samples and incorporate industry-specific or regulatory factors.